2020
DOI: 10.1371/journal.pone.0243343
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, comorbidities and survival analysis of young adults hospitalized with COVID-19 in New York City

Abstract: This study reviewed 395 young adults, 18–35 year-old, admitted for COVID-19 to one of the eleven hospitals in New York City public health system. Demographics, comorbidities, clinical course, outcomes and characteristics linked to hospitalization were analyzed including temporal survival analysis. Fifty-seven percent of patients had a least one major comorbidity. Mortality without comorbidity was in 3.8% patients. Further investigation of admission features and medical history was conducted. Comorbidities asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
(37 reference statements)
6
40
4
Order By: Relevance
“…Additionally, we were able to assess thirty-day patient statuses, including subsequent hospital encounters, and to capture a range of disease outcomes. The previously published research articles describing risk factors for severe COVID-19 in young adults included a combined total of fewer than 1,500 patients, and primarily included information from the diagnostic encounter [6][7][8]. Our findings constitute a substantial addition to the existing knowledge base because we not only included data for young adults diagnosed at both inpatient and emergency department encounters, but also collected longitudinal outcome data, thus allowing us to characterize patients at all stages of disease progression.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we were able to assess thirty-day patient statuses, including subsequent hospital encounters, and to capture a range of disease outcomes. The previously published research articles describing risk factors for severe COVID-19 in young adults included a combined total of fewer than 1,500 patients, and primarily included information from the diagnostic encounter [6][7][8]. Our findings constitute a substantial addition to the existing knowledge base because we not only included data for young adults diagnosed at both inpatient and emergency department encounters, but also collected longitudinal outcome data, thus allowing us to characterize patients at all stages of disease progression.…”
Section: Plos Onementioning
confidence: 99%
“…Specifically, the proportion of young-adult COVID-19 patients in the Houston area has markedly increased over time [5]. Among studies in young adults, only a few have incorporated longitudinal clinical data [6][7][8]. However, these studies were either conducted with small sample size [6,8] or only reported preliminary data on the proportion of patients who experienced the composite event of death and mechanical ventilation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the rates Cunningham et al found using a national all-payer hospital database in adults aged 18–34 years admitted to US hospitals, namely, 21% required intensive care and 2.7% died [ 14 ]. Notably, Altonen et al reported an even higher mortality rate of 13% in this population in New York City public hospitals [ 15 ]. Recent data from the from the Spanish Ministry of Health show that more than 2 million patients between 20 and 60 years of age have been infected with SARS-CoV-2 and 3.9% of them have required hospitalization; 0.39% (10% of hospitalized patients) have been admitted to the ICU with an overall mortality rate of 0.1% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only baseline comorbidity that carried a significant risk in our study was heart disease. Numerous studies have shown that patients with underlying heart diseases have higher odds of death from COVID-19 [23][24][25][26] and it has also been described as a risk factor in a younger population [15]. The worse prognosis of COVID-19 in patients with a history of heart disease could be related to elevated expression of ACE2 and a higher baseline production and release of renin.…”
Section: Discussionmentioning
confidence: 99%